P12 Measuring the effectiveness of a multidisciplinary NASH Clinic. (6th September 2011) - Peake, C M; Cobbold, J F L; Anstee, Q M; Yee, M; Thursz, M R
Abstract : Introduction: Non-alcoholic fatty liver disease (NAFLD) and specifically non-alcoholic steatohepatitis (NASH) are associated with both increased liver-related and cardiovascular morbidity and mortality. A multi-disciplinary, individualised approach targeting the complex pathogenesis of the disease has been employed in a tertiary/secondary care setting. The aims of this study were (1) to investigate the effectiveness of a multi-disciplinary NASH clinic by assessing the change in liver disease markers and risk factors for liver-related and cardiovascular mortality over time, and (2) to identify factors that influence patient response to treatment. Method: This was a retrospective survey of current clinical practice. NASH/NAFLD was defined histologically or NAFLD by echogenic liver on ultrasound with raised aminotransferase values in absence of a significant alcohol history or other hepatic co-morbidities. Interventions included: lifestyle advice; dietetic input; exercise classes; pharmacological therapy; bariatric surgery. Clinical and anthropometric data were collected including serum ALT, BMI, HBA1c, systolic blood pressure, total and HDL cholesterol values and analysed for the cohort overall and for patients who were obese, diabetic, hypertensive and dyslipidaemic respectively. Responders to treatment were defined as those with >10% decrease in ALT over the study period. Univariate and multivariate analysis were conducted to analyse baseline factors influencing patient response. Results: 145 patients were included with median follow-up of 12.5 months (range 3–44 months). Overall improvement was seen in ALT (−15%, p=7×10 −6 ), BMI (−1.5%, p=6×10 −6 ) and total cholesterol (−4.1%, p=0.006). BMI improved by >10% in 8%, by >7% in 16% and by >5% in 23% of patients. Patients categorised by abnormal baseline ALT, baseline obesity, baseline hypertension and baseline dyslipidaemia had improvements in ALT (−19%, p=1×10 −7 ), BMI (−2.4%, p=0.001), systolic BP (−5.4%, p=3×10 −4 ) and total cholesterol (−5.5%, p=0.002) respectively. Patients with type 2 diabetes made up a higher proportion of those who did not respond or who progressed compared to those who responded on univariate analysis (p=0.02), but this was not significant on multivariate analysis. Moreover, patients with diabetes did not have a significant decrease in ALT (−8%, p=0.06). Conclusion: The management framework adopted by the multidisciplinary NASH clinic is effective at reducing ALT overall. Cardiovascular risk factors were improved overall. Diabetic patients had a poor ALT response. These data support the use of a multidisciplinary NASH clinic, but long-term outcome data are awaited.